SIFAT FISIK-MEKANIK PAPAN PARTIKEL DARI LIMBAH FINIR BERDASARKAN WAKTU KEMPA DAN KONSENTRASI UREA FORMALDEHIDA - Aprillia, Aprillia; Dirhamsyah, M; Indrayani, Yuliati (JURNAL HUTAN LESTARI, 2019)
This study aims to examine the physical and mechanical properties of particle board from veneer waste based on the press time and concentration of urea formaldehyde, as well as to determine the best pressing time and adhesive concentration, so as to produce physical and mechanical properties that meet JIS A 5908: 2003 standards. The method used in this research were a factorial experiment in random design complete (RAL) with two factors are factor A (pressing time) consists of 7 minutes and 9 minutes, and factor B (urea formaldehyde concentration) consists of concentrations of 12%, 14% and 16%. The particle board size is 30 cm x 30 cm x 1 cm with a target density of 0,8g/cm3 and pressed at 165°C with a pressure of 30 kg/cm2. The results showed that density values 0,7640 gr/cm³, water content 8,4509%, water absorption 40,4108%, thickness development 9,9308%, MOE 19.290,5877 kg/cm², MOR 370,5011 kg/cm², IB 2,9925 kg/cm², the screw holding strength 146,7145 kg. In general, all test values meet the JIS A 5908: 2003 standards except thickness swelling and MOE. The best particle board is a particle board made of with a pressing time of 9 minutes with a concentration of urea formaldehyde of 16%.Keywords: pressing time, urea formaldehyde concentration, particle board, veneer waste